Development of Lemongrass-infused Calamansi Ginger concentrate - Sevilla, Meghan Kristen F. (College of Home Economics, University of the Philippines Diliman, 2021)
This study aimed to develop a lemongrass-infused calamansi ginger concentrate by modelling and optimizing the formulation. Response surface methodology (RSM) with a central composite design (CCD) was used to model the acceptability of the product, and to optimize the process and formulation parameters, i.e., infusion time and amount of lemongrass. Statistical models were generated that predicted effects of infusion time and amount of lemongrass on consumer acceptability of the ready-to-drink (RTD) beverage prepared from the developed concentrate. Verification experiments were used to validate the accuracy of the predictive models. Optimal consumer acceptability in terms of appearance and aroma was achieved with 20 min infusion time and 100g lemongrass in producing the concentrate. Verification experiments confirmed that the statistical models accurately predicted responses. The consumer acceptability scores, physicochemical, proximate, and microbial properties of the upscaled batch showed no significant (p>0.05) differences between the replicated production runs indicating that the upscaling process was standardized.